The Analysis of Digital Literacy of Teachers in PGRI 363 Junior High School in Pondok Petir - Permana, Putut Said; Sesriyani, Lodya; Prasetyawan, Enggar; Anwar, Saiful; Rusmaini, Rusmaini; Zubaidah, Siti (Journal of Community Research and Service, 2022)
This PkM aims to socialize digital literacy as an effort to provide an understanding of the digital world that is directly related to learning used in online learning. Since the world was hit by the COVID-19 pandemic, almost all lines of life have changed. Slowly but surely, people must begin to get used to this situation, including the education. In online learning, teachers face various challenges that come from both teachers and students. The most perceived challenge by teachers is to motivate students in learning. This PkM was conducted by 5 lecturers and involved 5 students who were running a field practice program at SMP PGRI 363 Pondok Petir. This activity lasts for 3 days on November 9-11, 2021. This activity begins with observing the needs of teachers in terms of teaching and learning activities in the classroom. After making observations, it was found that teachers and students need a variety of activities that can reduce boredom when learning online. The activity was continued by socializing material about the importance of digital literacy to access information, then the next day the teacher was given the opportunity to develop various activities that involve student activities in digital learning.